Leptin Gene as Potential Gene for Molecular Selection on Cattle in Indonesia - Widya Pintaka Bayu Putra; Rhesti Indriastuti (Indonesian Center for Animal Research and Development, 2017)
Genetic improvement in beef and dairy cattle which can increase meat and milk production can be conducted through livestock selection based on molecular technique using leptin gene. The leptin gene is located on the fourth chromosome and consists of three exons and two introns. The leptin gene serves to produce the leptin hormone secreted by fat tissue. High concentrations of leptin hormone can increase feed intake and body metabolism thereby increasing livestock productivity. This paper describes the leptin gene including structure, mechanism of leptin hormone and polymorphisms in cows. These polymorphisms occur in the promoter, intron and exon sections associated with body and carcass weight and milk production in some cattle breed. Therefore, leptin gene can be used for selection towards increasing cattle productivity. Utilization of leptin gene can be done by single nucleotide polymorphism (SNP) identification on the whole structure of leptin gene and to observe its effect on characteristics of cattle production in Indonesia.